Solvent-free enzymatic process for biolubricant production in continuous microfluidic reactor. (15th April 2015) - Madarász, J.; Németh, D.; Bakos, J.; Gubicza, L.; Bakonyi, P.
Abstract: Synthesis of environmental-friendly chemicals attracts high attention nowadays, especially when naturally occurring compounds and industrial side-products are utilized. This paper reports for the first time on biolubricant (isoamyl oleate) production via continuous enzymatic reaction in microfluidic reactors (H-Cube™, X-Cube™). The proposed esterification was catalyzed using Novozym 435 enzyme, while substrates used were renewable raw materials: oleic acid and isoamyl alcohol. The latter is a main component of fusel oil, the by-product of bioethanol technology. The aim of this investigation was to evaluate the feasibility of the above-mentioned bioconversion in solvent-free media, considered as a cleaner way ahead. The successful applicability of miniaturized, continuous flow reactors for the biocatalytic reaction was demonstrated since isoamyl oleate could be obtained as long as 144 h in the H-Cube™ without any significant loss of enzyme activity. The highest conversion (98%) was achieved in X-Cube™. The results indicated that biocatalysts loading, residence time of reactants and dewatering of reaction mixture are important parameters and facilitate improved process efficiency. Highlights: A biolubricant was produced by enzymatic esterification. The applicability of miniaturized continuous flow reactors was demonstrated. Solvent free system was suitable for isoamyl oleate production.